Effect of non-metallic inclusions on AISI 4140 fatigue strength. (October 2022) - Scorza, Daniela; Carpinteri, Andrea; Ronchei, Camilla; Vantadori, Sabrina; Zanichelli, Andrea
Highlights: A fatigue strength assessment procedure for steels with inclusions is proposed. Such a procedure implements a defect content analysis and the area -parameter model. The multiaxial critical plane-based criterion by Carpinteri at al. is also implemented. A return period optimisation, in terms of fatigue strength estimations, is performed. An experimental campaign is analysed to evaluate the accuracy of the above procedure. Abstract: In the present paper, a procedure for fatigue strength assessment of high strength steel (AISI 4140) containing non-metallic inclusions (NMIs) is proposed. Such a procedure implements: (i) a defect content analysis, (ii) the area -parameter model, and (iii) the multiaxial critical plane-based criterion by Carpinteri at al. According to the defect content analysis, the distribution of NMIs is determined in two cross-sections perpendicular to the maximum principal stress directions under normal and shear uniaxial cyclic loadings. The return periods, obtained optimising the accuracy of the procedure in terms of fatigue strength estimation, are determined by taking into account five different prediction volumes. The results achieved through the proposed procedure are compared with both the experimental data and the results obtained employing the Carpinteri et al. criterion without optimisation.